The dramatic game. a strategy to improve oral expression - Soler Guerrero, Gloria Isabel; López Vargas, Leidy Yanet; Duarte Acero, Jorge Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article reviews the results of a research carried out at “San Rafael” Educational Institution in the municipality of Rondón (Boyacá) in the Granada Oriente and Páramo branches; through reflective work, based on a diagnosis made through the application of interviews and direct observation, evidencing a lackof command of verbal and gestural language used in communicative processes. This action type research, with a qualitative approach, with the objective of evaluating the changes presented in the oral expression with the implementation of the dramatic game as a didactic strategy in the second-grade students; structured in three phases: first; identify the problem and design of workshops; second; application of workshops; third; Analysis and evaluation of results. The proposed methodology; shows results in terms of voice tone, vocabulary increase and body expressions in communicative situations. Evidence significant progress in the oral expression of the population under study.